Nonobstetrical Acute Abdomen during Pregnancy as a Consequence of Colorectal Carcinoma Perforation: Case Report and Review of the Literature - Žana Žegarac; Željko Duić; Sandra Stasenko (Case Reports in Gastrointestinal Medicine)
Colorectal carcinoma is a rare but potentially fatal disease complicating pregnancy. It occurs most frequently in patients aged 50, although some studies report increasing incidence in women under the age of 40. Diagnosis of colorectal cancer during pregnancy is usually made at an advanced stage due to unspecific symptoms. We will present a case of an acute abdomen during pregnancy due to colorectal carcinoma perforation in a 33-year-old patient in her 26th week of gestation. Because of her abdominal condition, left hemicolectomy with colostomy was performed. Two hours after surgery, the patient gave birth to a male child weighing 910 g with an Apgar score of 2/6. The pathohistological finding indicated adenocarcinoma of the colon in Dukes stage B.